Glazes, colourants and decorations in early Islamic glazed ceramics from the Vega of Granada (9th to 12th centuries CE). (October 2018) - Molera, Judit; Carvajal López, Jose Cristóbal; Molina, Glòria; Pradell, Trinitat
Abstract: This paper presents an analysis of glazes of vessels unearthed in archaeological excavation in the Vega of Granada (south-east Spain) and that can be dated between the 9th and the 12th centuries AD. The material analysed includes the first glazed ceramics produced in Al-Andalus after the Islamic occupation of the Peninsula. From a very early period (mid to late-9th century) there is a coexistence of lead-alkaline monochrome (green and honey) glazed vessels, and of polychrome decorated (green, white and brown) tin-glazed, wares early examples of the so called green and manganese wares. From the 10th century onwards honey lead-alkaline glazed vessels often with manganese-painted decorations are found. The chemical composition of the ceramic pastes, glazes and decorations as well as of the microcrystallites present in the glazes is obtained from polished cross sections of the glazes by SEM-EDS, OM and EPM. Information about the materials and methods of production is discussed and compared to contemporary productions from other areas in Al Andalus and also to later productions. Highlights: Early Islamic glazed wares are analysed with OM, SEM-EDX and EPM. Lead glazes were raw mixtures over biscuit or fired mixtures over raw ceramic. Tin glazes were applied over biscuit fired bodies. Pigment and lead oxide mixtures were applied over the tin glazes for the colour decorations. There is a chronological change in lead glaze composition.